DECISIONS OF THE CONSTITUTIONAL COURT OF THE RUSSIAN FEDERATION AS A SOURCE OF CIVIL PROCEDURAL LAW - Vladimir Khudoba (Krymskij Naučnyj Vestnik, 2016)
The article is devoted research of the legal nature of decisions of The Constitutional Court of the Russian Federation (hereinafter — CC RF), which he interprets the provisions of the Constitution or laws of the Russian Federation, and also decisions regarding the constitutionality of legislative acts. In the process of study of the subject, the author correlated the competence, the content and form of the activities of the authority of the constitutional control have the same characteristics of legislative acts. Giving the characteristic of the RF constitutional court, revealing his features, after a thorough analysis of its decisions, as well as taking recent research sources and publications on this issue, both domestic and foreign authors, judiciary practice and the civil procedure law, the author comes to the conclusion that the sources of law include only those decisions in which the constitutional court came to the conclusion that a particular law or normative act (partially or fully) does not meet the Constitution of the Russian Federation. Thus, according to the author, all decisions of the constitutional court, which he recognizes a particular norm of civil procedural law unconstitutional, are not only normative, but also are sources of civil procedural law.